Solar cell, solar cell module and manufacturing method thereof - WU, CHIEN-SHU; CHAN, I-MIN; LEE, HSIAOING (2016)
A solar cell includes a p-n junction, a substrate, a transparent conductive film and a bus bar. The transparent conductive film is disposed on the surface of the substrate and an opening is disposed in the transparent conductive film. The bus bar fills up the opening so that its bottom surface is substantially level with the bottom surface of the transparent conductive film.